Industrialization and political affinity : industrial policy in Brazil - Nelson, Roy C. (Routledge, 1995)
Introduction. The computer industry. The pharmaceutical industry. Political characteristics of the corpos técnicos. The other variables in the model. Application of the argument to other cases.